Impact of Knowledge Sharing and Knowledge Retention on Employees Development through the Mediation of Sustainable Competitive Advantage and Moderation of Transformational Leadership - Hanif, Muhammad Imran; Sagheer, Hiba; Mehak, Sameen (International Review of Management and Marketing, 2020)
In advanced time, firms realize that procuring the past information and sharing them among the representatives will increment the improvement and development of the employees and it is the path to pick up a Sustainable Competitive Advantage in a showcase. The study points to center on the development of the workers through supporting the competitive edge. This could be done by legitimate utilize of past information and encounter which is procured and shared among the individuals of an organization. Leaders also play an imperative part within the Knowledge Sharing and Retaining but Transformational Leaders does not make an energetic environment through which they can offer assistance to form sound learning handle. It is since Transformational Leaders frequently don't know almost the conduct and states of mind of the representatives, their needs and wishes. This study is quantitative and close-ended questions were utilized to expound the relationship of the factors. Information was collected from a test estimate of 200 respondents of the telecommunication sector. The regression technique was used to test the hypothesis relationship. The findings of this study show that Knowledge Sharing, Knowledge Retention has a significant positive relation with Employee Development and Sustainable Competitive Advantage mediates significantly between them. While, Transformational Leadership does not significantly moderate the relation between Knowledge Sharing, Knowledge Retention, and Sustainable Competitive Advantage. Further, it describes limitations and the direction for the future. Keywords: Knowledge Sharing, Transformational Leadership, Sustainable Competitive Advantage, Knowledge Management, Employee Development JEL Classifications: M1, L1, M0 DOI: https://doi.org/10.32479/irmm.9931